Elementary Analysis on the Characteristics and Causes as Well as Countermeasures of Juvenile Delinquency (Asian Journal of Social Science Studies, 2022)
In recent years, one by one, shocking cases of juvenile delinquency have gradually entered the public eye, and governing the problem of juvenile delinquency has become an important task for the state and society according to the law. there are profound reasons behind juvenile delinquency .as a law student, it is necessary to analyze the characteristics, causes and countermeasures of juvenile delinquency from the various problems encountered by juveniles on their way to grow up, which is useful to effectively prevent juvenile delinquency and guide the healthy growth of juveniles.